Identification and characterization of a novel SoxB2 gene in Litopenaeus vannamei and its potential roles in response to ammonia-N stress and post-exposure recovery - Hongbiao Zhuo; Jianyong Liu (Aquaculture Reports, 2023)
Increased concentrations of ammonia-N can cause seriously physiological harm to crustaceans, especially farmed shrimp (Litopenaeus vannamei). Ammonia-N is generally removed by water change, and will gradually accumulate for unconsumed feed. However, the underlying adaptation mechanism of shrimp under such environmental conditions is still not fully understood. A novel Sox gene expressed differentially in previous comparative transcriptome studies was characterized in this study, designated as LvSoxB2–1. The LvSoxB2–1 encodes a protein of 420 amino acids, sharing the highest identity with the Chinese mitten crab (Eriocheir sinensis) Sox14b. The expression level of LvSoxB2–1 was higher in fertilized egg and cleavage stage of early embryonic development and declined in the blastula stage, which showed no significant difference compared with the subsequent stage. During larval development, LvSoxB2–1 increased significantly in nauplius stage III and zoea stage I and then restored to the initial level. LvSoxB2–1 was highly expressed in the gills, followed by eyestalks and brain ganglion. Results of subcellular localization have shown that LvSoxB2–1 is a nuclear-localized protein. In the ammonia-N stress and post-exposure recovery experiments, LvSoxB2–1 mRNA significantly increased in the gills, hepatopancreas, and hemocytes. The total hemocyte counts (THC) of shrimp was decreased through LvSoxB2–1 RNA interference (RNAi). Moreover, the inhibition of LvSoxB2–1 significantly exacerbated the hepatopancreas pathology and reduced the survival rates of shrimp exposed to ammonia-N. Dual-luciferase reporter assay confirmed the activation of the Wnt/β-catenin pathway by LvSoxB2–1. Under ammonia-N stress and recovery after exposure, LvSoxB2–1 silencing could decrease the expression of Wnt/β-catenin signaling molecules (β-catenin and Pangolin) and Rh protein in L. vannamei, with the higher malonyldialdehyde (MDA) and protein carbonylation (PCO) levels and hemolymph ammonia-N and urea contents. These results suggested that LvSoxB2–1 played positive roles in oxidative stress responses and ammonia-N excretion through the Wnt/β-catenin pathway.